2018
DOI: 10.17344/acsi.2017.3953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Copper Alloying on Electro-Catalytic Activity of Nickel for Ethanol Oxidation in Alkaline Media

Abstract: In this research, the electro-catalytic activity of nickel-copper (Ni-Cu) alloy towards oxidation of ethanol and its possible redox process were investigated in alkaline solution. For this purpose, cyclic voltammetry, chronoamperometry and electrochemical impedance spectroscopy techniques were employed. According to the cyclic voltammetry studies, Ni- Cu alloy compared to pure nickel can demonstrate a significantly higher response for ethanol oxidation. So, the enhancement of the anodic peak current correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…According to the fitted curve, the diffusion current followed Cottrellian behavior. 44 In addition, as the mass percentage of Cl-GQDs was changed from 1% to 5%, the photocurrent density of Cl-GQDs/In 2 O 3 was increased and then decreased. It was because Cl-GQDs of 1 wt%, 3 wt% and 5 wt% had a "positive effect" that could facilitate the separation of photogenerated carriers and store photogenerated electrons.…”
Section: Resultsmentioning
confidence: 97%
“…According to the fitted curve, the diffusion current followed Cottrellian behavior. 44 In addition, as the mass percentage of Cl-GQDs was changed from 1% to 5%, the photocurrent density of Cl-GQDs/In 2 O 3 was increased and then decreased. It was because Cl-GQDs of 1 wt%, 3 wt% and 5 wt% had a "positive effect" that could facilitate the separation of photogenerated carriers and store photogenerated electrons.…”
Section: Resultsmentioning
confidence: 97%
“…A cyclic voltammogram curve is obtained by plotting current versus potential. In the ensuing cyclic voltammogram, there are two distinct regions: anodic (positive current values) and cathodic (negative current values), which represent the oxidation and reduction reactions, respectively [35]. On this graph, the peak current indicates the potential at which the electrode reactions occur.…”
Section: Band-bending In Tmc and Tmh Heterostructures Synthesized By ...mentioning
confidence: 99%
“…Although nickel possesses electrocatalytic properties, and due to these properties is often used in industry, the overvoltage of hydrogen evolution (HER) on the nickel electrode is quite high, causing an increase in the energy consumption during its use. Therefore, in order to reduce overvoltage, nickel is often doped with other elements such as Mo [11], Co [12], P [13], Cu [14], etc. Besides, the results of water electrolysis on titanium and molybdenum electrodes from neutral (NaCl) and alkaline (NaOH) electrolytes showed that addition of Mo(VI) ions into the electrolyte activated HER [15].…”
Section: Introductionmentioning
confidence: 99%